2021
DOI: 10.24251/hicss.2021.201
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Production Systems - Requirements and Influences on Logistics Planning for Decentralized Production Structures

Abstract: In the context of the digital transformation of industry and within the framework of Industrie 4.0 and Factory Planning 4.0, new production-organizational principles with decentralized, modular and freely linked production cells are increasingly being discussed. The principle of matrix production with categorized and standardized workstations offers an extremely versatile production environment. It can be used to meet the challenge of an increasing number of product variants in variable quantities. This concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A detailed comparison of the respective forms of production organisation and their advantages and disadvantages can be found in Schmidtke et al (2021). This paper focuses on assessing the resilience of matrix production systems and the influences of different material supply strategies and requirements for smart order control and logistics processes.…”
Section: Figure 2 Comparison Of Production Concepts On the Basis Of P...mentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed comparison of the respective forms of production organisation and their advantages and disadvantages can be found in Schmidtke et al (2021). This paper focuses on assessing the resilience of matrix production systems and the influences of different material supply strategies and requirements for smart order control and logistics processes.…”
Section: Figure 2 Comparison Of Production Concepts On the Basis Of P...mentioning
confidence: 99%
“…It will allow to successively investigate different material supply strategies with regard to the resilience and performance of the production system. In reflection of Schmidtke et al (2021), the process sequence as well as the distribution of different product variants within the use case has been adapted and validated in dialogue with experts from the automotive sector. The process model was discussed and edited in two interviews, each interview including members of German automobile manufacturers (from the areas of production and program planning).…”
Section: Model Concept and Use-case Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the system can convert itself, scale, and, control capacity utilization and bottlenecks. A sketch of the matrix production can be seen in Fig 3 . As this concept is relatively new, it is suggested that its control logic is an open research question [30].…”
Section: Emerging Concepts On Shop-floor Automationmentioning
confidence: 99%